Kecerdasan Buatan pada Fotografi sebagai Godaan Etika bagi Jurnalis - Aditia Noviansyah (Warta Ikatan Sarjana Komunikasi Indonesia, 2025)
Abstract - We can feel the development in the world of journalistic photography from changes in camera technology, such as the transformation of analog cameras to digital cameras. In the era of digital cameras, it also became the next foothold where we were shown changes in the way journalistic photographers work. At that time, journalistic photographers were able to quickly send a photo to the editorial room via the internet network. In addition, journalistic photographers do not only work to take pictures, journalistic photographers can also double as videographers. This change in work is caused by cameras that are already capable of doing the job. Furthermore, artificial intelligence (AI) technology is also included in camera technology. AI technology greatly helps the technical role of journalistic photographers, but on the other hand, AI technology can really tempt journalistic photographers' ethics to violate journalistic rules if done unwisely, because it ignores a fact that occurs in one event. This qualitative research uses the phenomenological theory method, as explained by Alfred Schutz who presents a unique and profound perspective on meaning in human interaction. Schutz views that social reality is not something that is purely objective, but is formed through the subjective experiences of individuals in everyday life. This research was conducted by collecting data through observation and documentation. So it can be concluded that the form of journalistic photography must uphold intact ethics or legal norms, both in terms of its actions, its creation and its broadcasting worthiness.Keywords: Journalistic Photography, Artificial Intelligence, Camera Technology, Journalistic of Ethics; Photo Editing Abstrak – Perkembangan fotografi jurnalistik bisa kita rasakan dari perubahan teknologi kamera, seperti halnya transformasi kamera analog ke kamera digital. Di era kamera digital juga menjadi pijakan selanjutnya di mana kita diperlihatkan perubahan cara kerja fotografer jurnalistik. Fotografer jurnalistik sudah dapat mengirim cepat sebuah foto ke ruang redaksi melalui jaringan internet. Selain itu, fotografer jurnalistik tidak bekerja untuk memotret saja, pekerjaan fotografer jurnalistik juga bisa merangkap sebagai videografer. Perubahan kerja itu disebabkan oleh kamera yang sudah mumpuni untuk melakukan pekerjaan tersebut. Selanjutnya teknologi kecerdasan buatan atau artificial intelligence (AI) juga masuk dalam teknologi kamera. Teknologi AI sangat membantu peran teknis pekerjaan fotografer jurnalistik, tetapi di sisi lain teknologi AI bisa menggoda etika fotografer jurnalistik untuk melanggar kaidah jurnalistik, karena mengesampingkan fakta yang terjadi padaperistiwa. Penelitian kualitatif ini menggunakan metode teori fenomenologi, sebagaimana dijelaskan oleh Alfred Schutz yang menghadirkan sudut pandang yang unik dan mendalam tentang makna dalam interaksi manusia. Schutz memandang bahwa realitas sosial bukanlah sesuatu yang bersifat objektif semata, melainkan dibentuk melalui pengalaman subjektif individu dalam kehidupan sehari-hari. Penelitian ini dilakukan dengan mengumpulkan data-data melalui observasi dan dokumentasi. Kesimpulan penelitian adalah, foto jurnalistik harus memegang etika baik dari segi perbuatan dan pembuatannya.Kata kunci: Fotografi Jurnalistik, Kecerdasan Buatan, Teknologi Kamera, Etika Jurnalistik, Penyuntingan Foto